Correlating Neuroimaging and CNVs Data: 7 Years of Cytogenomic Microarray Analysis on Patients Affected by Neurodevelopmental Disorders - Milone, Roberta; Cesario, Claudia; Goldoni, Marina; Pasquariello, Rosa; Fusilli, Caterina; Giovannetti, Agnese; Giglio, Sabrina; Novelli, Antonio; Caputo, Viviana; Cioni, Giovanni; Mazza, Tommaso; Battaglia, Agatino; Bernardini, Laura; Battini, Roberta (Journal of Pediatric Genetics, 2020)
The aim of this study was to evaluate the relationship between neurodevelopmental disorders, brain anomalies, and copy number variations (CNVs) and to estimate the diagnostic potential of cytogenomical microarray analysis (CMA) in individuals neuroradiologically characterized with intellectual developmental disorders (IDDs) isolated or associated with autism spectrum disorders (ASDs) and epilepsy (EPI), all of which were identified as a “synaptopathies.” We selected patients who received CMA and brain magnetic resonance imaging (MRI) over a 7-year period. We divided them into four subgroups: IDD, IDD + ASD, IDD + EPI, and IDD + ASD + EPI. The diagnostic threshold of CMA was 16%. The lowest detection rate for both CMA and brain anomalies was found in IDD + ASD, while MRI was significantly higher in IDD and IDD + EPI subgroups. CMA detection rate was significantly higher in patients with brain anomalies, so CMA may be even more appropriate in patients with pathological MRI, increasing the diagnostic value of the test. Conversely, positive CMA in IDD patients should require an MRI assessment, which is more often associated with brain anomalies. Posterior fossa anomalies, both isolated and associated with other brain anomalies, showed a significantly higher rate of CMA positive results and of pathogenic CNVs. In the next-generation sequencing era, our study confirms once again the relevant diagnostic output of CMA in patients with IDD, either isolated or associated with other comorbidities. Since more than half of the patients presented brain anomalies in this study, we propose that neuroimaging should be performed in such cases, particularly in the presence of genomic imbalances.
Keywords: synaptopathies; intellectual developmental disorders; autism spectrum disorders; epilepsy; brain anomalies